PEMBUATAN BIODIESEL DENGAN REAKTOR BERSIRKULASI SEDERHANA MENGGUNAKAN KATALIS KOH - Rudi Hartono; Yus Rama Denny; Deni Sulaiman Ramdhani; Lusiani Dewi Assaat; Agie Wildha Priakbar; Wusda Hetsa Ribawa (Jurnal Teknologi, 2023)
The high use of petroleum causes petroleum reserves to deplete, this is because petroleum is a natural resource that cannot be renewed. The purpose of this research is to make biodiesel using a simple circulating reactor and analyze biodiesel so that biodiesel is obtained which is suitable for use and according to general biodiesel standards. This research is limited by several variables consisting of fixed variables, namely raw materials in the form of 20 liters of used cooking oil, 100 g of KOH catalyst, and a reaction temperature of 600C, while the independent variables are the circulating stirring time for 55, 60, and 65 minutes, and the ratio feeds were 17% v/v and 21% v/v methanol. The stages of research carried out are preparation of raw materials, manufacture of biodiesel, and testing of biodiesel. Preparation of raw materials by preparing used cooking oil, KOH catalyst and methanol. Biodiesel production is carried out in a simple circulating reactor. The biodiesel tests carried out were density, viscosity, Free Fatty Acid (FFA) levels, Flash Point, Pour Point, cetane numbers, and Heat Heating Value (HHV). The research that has been done has produced biodiesel that complies with the SNI biodiesel standard. The density of biodiesel produced is in the range of 856.4-868.4 kg/m3. The resulting viscosity ranges from 2.98-3.41 cSt. The cetane number ranged from 57.3 to 58.2. Flash point ranges from 39.5-150.5oC. The pour point is around 9oC and the HHV is 9371-9490 kcal/kg. Generally, the yield of biodiesel produced is 75-90%. The optimum conditions for making biodiesel are at a variation of 17% v/v methanol with a reaction temperature of 60oC and a reaction time of 55 minutes.